The Causal Relationships among Competencies, Innovativeness, and Competitive Advantages Affecting the Performance of Smart Farmers in Nakhon Ratchasima, Thailand - Dejtanon, Isari; Ekasart, Ekarat; Pochatan, Suthanun; Pochatan, Suthasinee (Research Community and Social Development Journal, 2024)
Background and Objective: Business operations require innovation to raise the competitiveness of entrepreneurs. Therefore, this research aims to study importance and causal relationships between competencies, innovation capabilities, and competitive advantages that affect operating results. Additional, the study seek to create strategies for promoting and developing smart farmers in Nakhon Ratchasima Province. Methology: Mixed methods research, a sample size of 400 people was determined through multistage random sampling and a target group of 15 people selected through purposive sampling by using a closed-ended questionnaire with an index of consistency between the questions and the entire objective of 0.96. Field data were collected, distributed, and received back directly. Drafting strategy, organizing a strategy critique workshop, and data analysis were conducted by mean, standard deviation, structural equation analysis, hypothesis testing, SWOT Analysis, and TOWS Matrix. Results: 1) Smart farmers value innovation capabilities and competitive advantage. 2) Competencies directly and positively influence on innovation ability and competitive advantage. Innovation capabilities has a positive direct impact on the performance of smart farmers. Competitive advantage has a positive direct influence on the performance of smart farmers. Competencies have a positive indirect influence on the performance of smart farmers through innovation capabilities and competitive advantage. 3) Strategies of escalating the performance of smart farmers, Nakhon Ratchasima Province has 2 strategies: strategy for developing innovation competencies for smart farmers; and strategies for developing competency and competitiveness for smart farmer groups. Discussion: Competencies, innovation capabilities, and competitive advantage are an important thing that affects operations. These used to set strategies for optimization and add value for the agricultural industry positively, both directly and indirectly, at the national and global levels. Suggestion: Emphasis should be placed on creating a technological basis for smart farmers to develop, improve, and promote agricultural innovations appropriating with local wisdom which are in line with needs, economic, social, and environmental dimensions, and have been accepted for long term at all worldwide levels.